2015
DOI: 10.1002/jcp.25051
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of miR‐20a on p21: Two Mechanisms Blocking Growth Arrest in TGF‐β‐Responsive Colon Carcinoma

Abstract: Loss of response to TGF-β is a central event in the genesis of colorectal cancer (CRC), a disease that, in the majority cases, is refractory to growth inhibition induced by this cytokine. However, inactivating mutations at receptors and transducers from the TGF-β cascade occur only in approximately half of CRCs, suggesting the involvement of additional mechanisms altering the response to the cytokine. We have recently described the amplification of the 13q31 locus, where the miR-17-92 cluster maps, associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 53 publications
1
31
0
1
Order By: Relevance
“…However, only two of them, namely miR‐20a and miR‐31, exhibited upregulated expression patterns in response to VEGF treatment of the cells. It was recently reported by other investigators that miR‐20a and miR‐31 are noticeably upregulated in human tumors such as gastric cancer, nonsmall cell lung cancer, prostate cancer, and colorectal cancer . Findings by these investigators are consistent with our earlier report that VEGF produced by ovarian cancer cells can inhibit the production of TNFSF15 by endothelial cells in tumor tissues , as well as our findings here that miR‐20a and miR‐31 are involved in VEGF‐stimulated downmodulation of TNFSF15 activities in angiogenic endothelial cells.…”
Section: Discussionsupporting
confidence: 93%
“…However, only two of them, namely miR‐20a and miR‐31, exhibited upregulated expression patterns in response to VEGF treatment of the cells. It was recently reported by other investigators that miR‐20a and miR‐31 are noticeably upregulated in human tumors such as gastric cancer, nonsmall cell lung cancer, prostate cancer, and colorectal cancer . Findings by these investigators are consistent with our earlier report that VEGF produced by ovarian cancer cells can inhibit the production of TNFSF15 by endothelial cells in tumor tissues , as well as our findings here that miR‐20a and miR‐31 are involved in VEGF‐stimulated downmodulation of TNFSF15 activities in angiogenic endothelial cells.…”
Section: Discussionsupporting
confidence: 93%
“…miR-20a is a member of the miR-17-92 cluster (including miR-17, miR-18a, miR-19a, miR-20a, miR-19b-1 and miR-92a-1), which is commonly upregulated in malignant cancer and involved in carcinogenesis as the classical oncogene (16). Previous studies have reported upregulated expression levels of circulating miR-20a in malignant neoplasms, such as non-small cell lung cancer (NSCLC), and in cervical, hepatoma, colorectal and prostate cancers (17)(18)(19)(20)(21)(22). However, the association between the expression level of miR-20a and GC is rarely reported.…”
Section: Discussionmentioning
confidence: 99%
“…In glioblastoma cells, activation of miR-17-92 blunted TGFβ-induced gene expression signature ( 34 ). In addition, miR-20 targets CDKN1A (P21), an important negative regulator of cell cycle progression activated by TGFβ in colorectal cancer cells and blocks TGFβ-induced antiproliferative effect ( 35 ).…”
Section: Targeting Of Tumor-suppressive Pathways In Cancer By Mir-17-mentioning
confidence: 99%